Development of an ethnosteam-based critical thinking instrument - Kartika, Ika; Pitaloka, Bela Lola; Djufri, Elyas (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2025)
Culture-based education serves as a pivotal approach to managing student diversity by integrating cultural and social dynamics into the curriculum. Despite the recognized benefits of Ethno-STEAM, existing instruments rarely capture critical thinking within culturally contextualized science learning, revealing a clear gap in both research and practice. This study aims to develop and validate a critical thinking assessment instrument for Ethno-STEAM-based Integrated Science learning. Employing a Research and Development (R&D) design, the study involved 150 Physics Science education students. The ADDIE model guided the process, starting with a needs analysis through interviews and classroom observations, followed by iterative stages of design, development, pilot implementation, and evaluation. Instrument feasibility was assessed through validity, reliability, differentiability, and difficulty tests. The resulting 14-item instrument received expert ratings of 3.775 (material) and 3.804 (media), categorised as excellent. It demonstrated strong internal consistency (Cronbach’s alpha = 0.91), with 12 of 15 items (80%) meeting validity criteria (r > 0.195). Items 7, 10, and 15 were invalid due to lower coefficients. This instrument offers educators a culturally responsive tool to evaluate and enhance students’ critical thinking in Physics Science classrooms